Determinants of skate sprint cross-country skiing - Willis, S. J. (Montana State University, 2010)
Although previous research has established some correlates of sprint cross-country ski performance, it has not been determined which tests are the best determinants of sprint performance. There may be other tests or combinations of both lab- and field- based tests that are better able to determine sprint performance. PURPOSE: To investigate correlational relationships between a battery of test variables as predictors of skate roller skiing sprint performance in male and female junior and collegiate Nordic skiers. METHODS: Eleven female (Mean±SD; Age (yrs): 19±2; Height (cm): 167.6±5.5; Body Mass (kg): 64.9±7.0; Relative VO2MAX (ml/kg/min): 56.9±3.3) and nine male (Age (yrs): 18±1; Height (cm): 180.1±6.6; Body Mass (kg): 69.9±2.2; Relative VO2MAX (ml/kg/min): 70.6±4.8) competitive junior and collegiate skiers performed several lab tests including a maximal ski-striding treadmill test to exhaustion (VO2MAX, lactate threshold, TTE). Additional lab tests included upper body power (UBP) tests of 10 and 60 seconds, and lower body power (LBP) tests using a timing pad (1-jump, 4- jump, 60-jump vertical jump tests). Field-based roller skiing tests (40 m flying sprint, and 400 m sprint on a 200 m indoor track) were also completed. Skiers then performed a 1200 m skate roller ski sprint time trial on the indoor track. Pearson-Product Moment correlations assessed the linear relationship between all lab- and field-based variables and average race speed (m/sec) for time trial variables. Correlations were evaluated for both statistical significance (a = 0.01) and practical meaningfulness (r = 0.60). RESULTS: Treadmill variables correlated moderate to high with skate roller skiing sprint speed (r = 0.78 - 0.80) as did the indoor skate roller ski testing (r = 0.74 - 0.78). Recovery parameters of blood lactate measured 3 minutes post trials correlated moderately (r = 0.59 - 0.78) as well as both the UBP 10- and 60- second tests and the jump height variables of the vertical jump testing (r = 0.63 - 0.68 and r = 0.59 - 0.71). CONCLUSION: The correlations between the lab- and field-based tests and skate roller skiing sprint speed indicated that it is important to assess multiple testing methods with a variety of test durations to best determine skate sprint skiing performance.